Volume 1: Turbomachinery 1996
DOI: 10.1115/96-gt-444
|View full text |Cite
|
Sign up to set email alerts
|

A Boundary Layer Transition Model

Abstract: A new boundary layer transition model is presented which relates the velocity fluctuations near the wall to the formation of turbulent spots. A relationship for the near wall velocity frequency spectra is also established, which indicates an increasing bias towards low frequencies as the skin friction coefficient for the boundary layer decreases. This result suggests that the dependence of transition on the turbulent length scale is greatest at low freestream turbulence levels. This transition model is incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A similar model to that presented here, but using empirical correlations rather than analytical theory for the induction of the velocity fluctuations through the unsteady pressure field, has been used to predict transition previously (Savill, 1993(Savill, , 1994(Savill, , 1995aJohnson, 1994;Johnson and Ercan, 1996). In this work it was found that the model could be extended to adverse/favorable streamwise pressure gradients using the same unsteady pressure field model, as it is the effect of the streamwise pressure gradient on the time mean laminar boundary layer profile that results in an increase or decrease in the velocity fluctuation levels in an adverse or favorable pressure gradient, respectively.…”
Section: W Johnsonmentioning
confidence: 99%
“…A similar model to that presented here, but using empirical correlations rather than analytical theory for the induction of the velocity fluctuations through the unsteady pressure field, has been used to predict transition previously (Savill, 1993(Savill, , 1994(Savill, , 1995aJohnson, 1994;Johnson and Ercan, 1996). In this work it was found that the model could be extended to adverse/favorable streamwise pressure gradients using the same unsteady pressure field model, as it is the effect of the streamwise pressure gradient on the time mean laminar boundary layer profile that results in an increase or decrease in the velocity fluctuation levels in an adverse or favorable pressure gradient, respectively.…”
Section: W Johnsonmentioning
confidence: 99%
“…See also Seifert & Wygnanski (1995), Seifert (1997), Gostelow et al (1997), van Hest (1997) and Howell (1998). Computationally, direct simulations have yielded relatively little on adverse gradient effects, especially concerning their physical understanding, but empirically based modelling has been performed by Johnson (1997Johnson ( , 1998, Solomon, Walker & Gostelow (1996), Johnson & Ercan (1996) and Steelant & Dick (1996). Little basic theoretical nonlinear study without empiricism has been made for 'spots' until quite recently: see references later in this section.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the term 'spot' is used to denote a spot-like disturbance or, in two dimensions, a strip. 'Spot' propagation models are used in turbomachinery transition predictions (as described by Abu Ghannam & Shaw 1980;Gostelow et al 1993;Clarke, Jones & LaGraff 1994;Narasimha 1997;Johnson 1997; for instance) but are also relevant to other contexts with deep-transition physics (for example Smith & Bowles 1992;Li et al 1998;Savin, Smith & Allen 1999). Most of the many 'spot' experiments are for basic boundary layers under nominally zero pressure gradient, as discussed in the reviews in the references above.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson (1994) considered the effect of the fluctuating pressure field resulting from freestream turbulence on the near wall velocity profile within the laminar boundary layer. Experimental observations (Johnson and Ercan[1996]) of the near wall velocity fluctuations within laminar boundary layers show that the dominant wavelengths are much greater than the boundary layer thickness. Similar results have since been obtained theoretically by Mayle and Schultz [1997].…”
Section: Introductionmentioning
confidence: 99%